2021
DOI: 10.1177/2633190x211040622
|View full text |Cite
|
Sign up to set email alerts
|

Access to Institutional Credit by Farmers in Eastern India

Abstract: The supply of institutional credit plays an important role in promoting agricultural growth and also saving the farmers from the clutches of private moneylenders who charge exorbitantly high rates of interest and force them to live in perpetual debt trap. There has been a phenomenal increase in the flow of institutional credit to agriculture in the recent years but this has been quite uneven between regions. As of 2018–2019, the Southern Region had the highest share (43.0 %) in the institutional credit followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar to other developing nations, access to agricultural credit is crucial in Zimbabwe to enhance the well-being of these farmers. For example, smallholder farmers in Zambia [1,2], Pakistan [3], Kenya [4], and India [5] face many challenges in accessing financial services. Zimbabwe has been making an effort to enhance farmers' productive capacity by providing finance and investing in their physical and human capital since independence in 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other developing nations, access to agricultural credit is crucial in Zimbabwe to enhance the well-being of these farmers. For example, smallholder farmers in Zambia [1,2], Pakistan [3], Kenya [4], and India [5] face many challenges in accessing financial services. Zimbabwe has been making an effort to enhance farmers' productive capacity by providing finance and investing in their physical and human capital since independence in 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural finance is a decisive factor input in farming operations as it helps poor farmers to maintain their consumption of necessities, adopt advanced technology and raise their incomes [8]. The farmers in the Eastern region of India are generally small and marginal and have to depend largely on non-institutional sources of credit, which keeps them in a debt trap [9]. However, over time, the per-capita landholding of the Indian farm households is gradually declining and the dominance of small and marginal farmers is observed in major parts of India [10].…”
Section: Introductionmentioning
confidence: 99%
“…Credit is not a direct input in agricultural production; rather, it facilitates other inputs in the process (Sial et al, 2011). Many studies found that agricultural credit significantly impacts agricultural productivity/production (Haque and Goyal, 2021). As a result, agricultural credit raises cultural income and employment through the enhancement of production (Byerlee et al, 2009; Şimşir, 2012).…”
Section: Introductionmentioning
confidence: 99%